2020
DOI: 10.1016/j.gloplacha.2019.103055
|View full text |Cite
|
Sign up to set email alerts
|

AMOC and summer sea ice as key drivers of the spread in mid-holocene winter temperature patterns over Europe in PMIP3 models

Abstract: The mid-Holocene (6,000 years before present) was a warmer period than today in summer in most of the Northern Hemisphere. In winter, over Europe, pollen-based reconstructions show a dipole of temperature anomalies as compared to present-day, with warmer conditions in the north and colder in the south. It has been proposed that this pattern of temperature anomaly could be explained by a persisting positive phase of the North Atlantic Oscillation during this period, which was, however, not reproduced in general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
(58 reference statements)
1
5
0
Order By: Relevance
“…S6). The difference in AMOC strength between the mid-Holocene (6 ka) and the preindustrial period is 3-4 Sv, which is in agreement with several PMIP3 models 43 , providing further confidence in the result obtained from the calibration using the recent 30-90°N temperature reconstruction 45 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…S6). The difference in AMOC strength between the mid-Holocene (6 ka) and the preindustrial period is 3-4 Sv, which is in agreement with several PMIP3 models 43 , providing further confidence in the result obtained from the calibration using the recent 30-90°N temperature reconstruction 45 .…”
Section: Discussionsupporting
confidence: 86%
“…Yet the drivers of the AMOC dynamics for this period are still poorly understood. AMOC changes may be related to external forcings, meltwater input 43 , or other missing processes, such as changes in Mediterranean outflow during the so-called Sapropel S1 event 46 . In addition, following the "Zealandia switch" hypothesis 47 , a poleward shift of the SH westerlies between the early-and mid-Holocene would have led to global warming.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, such a response remains model dependent, as other processes, such as the reduction of sea ice export from the Arctic towards the North Atlantic, can lead to salinification of the convection sites and an increase in the AMOC (Born et al, 2010). When analysing the PMIP3 database for 6-ka BP, Găinuşă-Bogdan et al (2020) found that the ensemble mean of models does show an intensification of the AMOC for that period compared to preindustrial simulations. Such an increase is also corroborated by deep water reconstruction (Thornalley et al, 2013) and AMOC reconstruction (Ayache et al, 2018).…”
Section: Orbital Forcingmentioning
confidence: 98%
“…Modelled anomalies in atmospheric circulation during the mid-Holocene have, on the one hand, shown tendencies toward a more positive mean state of the NAO (e.g., Fischer and Jungclaus, 2010) and, on the other hand, a more negative AO (Park et al, 2018), with the latter result observed in multiple models as being connected to sea-ice loss. Nevertheless, the whole PMIP3 database exhibits a very model-dependent result (Găinuşă-Bogdan et al, 2020), highlighting very poor agreement on this topic within models.…”
Section: Orbital Forcingmentioning
confidence: 99%
“…The upper cell consists an upper limb of warm and salty northward surface flow (the North Atlantic warm current, up to 1200 m depth), and a lower limb of colder and deep southward flow (the North Atlantic Deep Water, 1500-4000 m depth) (Buckley and Marshall, 2016). The AMOC acts as a heat pump at the high latitudes as the meridional transportation brings warm water to the colder sub-polar and polar regions (Chen and Tung, 2018), then further modifies the climate in Northern Europe and the east coast of the North America (Gȃinuşȃ-Bogdan et al, 2020). It is responsible for producing about half of the global ocean's deep waters, sourced from the northern North Atlantic (Petit et al, 2021).…”
Section: Introductionmentioning
confidence: 99%